Accumulation of Abnormal Amyloplasts in Pulp Cells Induces Bitter Pit in Malus domestica - Qiu, Lina; Hu, Shanshan; Wang, Yongzhang; Qu, Haiyong (Frontiers in Plant Science, 2021)
Apple bitter pit primarily occurs during fruit ripening and storage; however, its formation mechanism remains unclear. Although it is considered that Ca2+ deficiency causes metabolic disorders in apples, there have been few studies on the mechanism of the bitter pit from the perspective of cell structure. At the fruit ripening stage, the fruit with a bitter pit on the tree was taken as the research material. In this study, the microscopic observation revealed numerous amyloplasts in the pulp cells of apples affected with bitter pit, but not in the healthy pulp. Furthermore, the results of fluorescence staining and transmission electron microscopy (TEM) revealed that the bitter pit pulp cells undergo programmed cell death (PCD), their nuclear chromosomes condense, and amyloplast forms autophagy. The cytoplasmic Ca2+ concentration in the healthy fruits was lowest near the peduncle, followed by that in the calyx, whereas it was highest at the equator. In contrast, the cytoplasmic Ca2+ concentration in apple fruits showing bitter pit disorder was lowest near the peduncle and highest in the calyx. Moreover, the cytosolic Ca2+ concentration in the flesh cells of apples with the bitter pit was much lower than that in the healthy apple flesh cells; however, the concentration of Ca2+ in the vacuoles of fruits with the bitter pit was higher than that in the vacuoles of healthy fruits. In summary, bitter pit pulp cells contain a large number of amyloplasts, which disrupts the distribution of Ca2+ in the pulp cells and causes PCD. These two processes lead to an imbalance in cell metabolism and induce the formation of a bitter pit.